Growth performance of Nile tilapia, Oreochromis niloticus, fed diets containing levels of pyridoxine and haematological response under heat stress - Teixeira, Caroline Pelegrina [UNESP]; Barros, Margarida Maria [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Fernandes, Ademir Calvo [UNESP]; Albers Koch, Joao Fernando [UNESP]; Padovani, Carlos Roberto [UNESP] (Wiley-Blackwell, 2012)
In order to assess the effect of dietary pyridoxine supplementation on the growth performance of Nile tilapia and the haematological response under heat stress, 192 fingerlings (8.41 +/- 0.22 g) were randomly distributed into eight tanks and fed practical diets supplemented with increasing levels of pyridoxine (0.0; 5.0; 10.0 and 20.0 mg of pyridoxal HCl kg-1 diet) for 91 days. The fish were then weighed and the diet was quantified to determine the growth performance [weight gain (WG), feed intake, feed conversion ratio, protein efficiency rate, protein retention (PR) and survival percentage]. Haematological analyses (red blood cell count, haematocrit, haemoglobin, total leucocyte and differentiation, mean corpuscular volume, mean corpuscular haemoglobin concentration, albumin, globulin and albumin/globulin ratio) were carried out and then 32 fish were transferred and subjected to heat stress (32 degrees C) for 3 days, after which the haematological parameters were analysed. The fish fed the unsupplemented diet showed the lowest WG and PR. For the normal growth and health of the Nile tilapia, the Pyridoxine requirement in a practical diet is 10.0 mg of pyridoxine HCl kg-1.
Keywords: anaemia; health; heat stress; Nile tilapia; vitamin B6